The Concept of Gharar in Business and Economic Practices - Muhammad Satrya Mutthaqin; Muhammad Yafiz (As-Syirkah: Islamic Economic & Financial Journal, 2026)
The concept of gharar is one of the fundamental principles in Islamic economics aimed at ensuring clarity, justice, and transparency in economic transactions. Gharar refers to excessive uncertainty, ambiguity, or lack of information within a contract that may cause injustice or potential loss to one of the contracting parties. Along with the rapid development of modern and digital economic systems, the potential presence of gharar has become increasingly complex, particularly in business practices such as e-commerce, pre-order systems, digital transactions, business contracts, and modern financial instruments. This study aims to examine the concept of gharar, its legal foundations, various forms, and its implications in contemporary business and economic practices. The research employs a qualitative method using a library research approach with descriptive-qualitative analysis. The findings indicate that the prohibition of gharar remains highly relevant in maintaining economic stability, protecting consumers, and promoting ethical business practices in accordance with Sharia principles. Therefore, the application of prudential principles, transparency, and contractual clarity is essential to minimizing gharar in modern economic activities.